Akuntabilitas Teknis Kebijakan Hunian Tetap (Huntap) Korban Erupsi Merapi 2010 di Cangkringan Kabupaten Sleman - Suranto Eko Widodo (Departemen Ilmu Pemerintahan Fisip Unhas, 2017)
The 2010 Merapi Eruption Victim Policy in Cangkringan Subdistrict is a relocation activity for residents living in Mount Merapi III Disaster Prone Areas which are no longer allowed to func- tion as dwellings because they are not safe from the threat of volcanic disasters. In addition to housing units, residents of Relocation also built public facilities and social facilities to support life in Huntap. Huntap's policy has been seen as successful and used as a model for disaster poli- cy. The success of the Huntap policy is one of the reasons for this study to look at Policy Ac- countability in disaster perceptions. This research is research with a case study approach which aims to describe the technical accountability of Huntap policies for victims of the Merapi erup- tion in 2010. The results revealed that the technical accountability of Huntap policies for victims of Merapi eruption in 2010 was very accountable where all indicators of technical accountability were related to input and policy output from planning, development, monitoring, and reporting can be done accountably. Community participatory approaches make implementing policies more accountable.